1996
DOI: 10.1007/bf02318962
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of somatic embryogenesis in zonal geranium

Abstract: A number of media constituents including sucrose, ammonium nitrate and plant growth regulators were evaluated in an attempt to improve somatic embryo production in zonal geranium (Pelargonium x hortorum) cv. Scarlet Orbit Improved. Somatic embryo production was characterized by the quantity and type of somatic embryo induced by the treatments. Sucrose at 4% supported the highest number of total somatic embryos while improving the proportion of the morphologically normal cotyledon-stage somatic embryos. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…Although there is a report about the regeneration of somatic embryos from suspension cultures in P. peltatum hybrids (Robichon et al 1997), the classification of regenerating structures as somatic embryos is unconvincing because it was not shown that the one presented structure was clearly separated from the parental tissue and that the other more developed structures were real bipolar structures. The only histological report clearly confirming the formation of bipolar structures in pelargoniums is the one involving somatic embryogenesis in the cultivar Madame Layal (Pelargonium x domesticum) (Wilson et al 1994). The results of this report are confirmed by the present study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although there is a report about the regeneration of somatic embryos from suspension cultures in P. peltatum hybrids (Robichon et al 1997), the classification of regenerating structures as somatic embryos is unconvincing because it was not shown that the one presented structure was clearly separated from the parental tissue and that the other more developed structures were real bipolar structures. The only histological report clearly confirming the formation of bipolar structures in pelargoniums is the one involving somatic embryogenesis in the cultivar Madame Layal (Pelargonium x domesticum) (Wilson et al 1994). The results of this report are confirmed by the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Such embryogenesis can lead directly to globular embryos through which the stock of embryogenic cells would be exhausted after a certain time. In the histological analysis of Wilson et al (1994), no pre-embryogenic determined cells were reported. The analysis shows that normal sub epidermal parenchyma cells are the origin of embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Average regeneration rates of up to 0.1 to 0.5 somatic embryos per explant have been achieved using petioles (Marsolais et al 1991;Haensch 1999). Therefore, most of the published work on somatic embryogenesis in Pelargonium hortorum is based on explants of very young seedlings, especially hypocotyls (Marsolais et al 1991;Slimmon et al 1991;Visser et al 1992;Qureshi and Saxena 1992;Gill et al 1993Gill et al , 1994Saxena 1996a, 1996b;Hutchinson et al , 1997aHutchinson et al , 1997bHutchinson et al , 2000Murthy et al 1996Murthy et al , 1999Wilson et al 1996;Croke and Cassels 1997;Senaratna et al 1999Senaratna et al , 2002Murch and Saxena 2001). Somatic embryos are defined, with general acceptance (Brown et al 1995), as new individuals that develop both a shoot apex and a discrete radicular end (Haccius 1978).…”
Section: Introductionmentioning
confidence: 95%